Role of Eryptosis in Hemorrhagic Stroke - Fang, Mei; Xia, Fan; Chen, Yuqi; Shen, Yuke; Ma, Lu; You, Chao; Tao, Chuanyuan; Hu, Xin (Frontiers in Molecular Neuroscience, 2022)
Erythrocytes undergo certain morphological changes resembling apoptosis during senescence or in an abnormal state/site, which is termed eryptosis. This process is characterized by phosphatidylserine exposure, membrane blebbing, and cell shrinkage. Eryptotic erythrocytes are subsequently removed via macrophage-mediated efferocytosis. In hemorrhagic stroke, blood within an artery rapidly bleeds into the brain tissue or subarachnoid space, resulting in severe neurological deficits. A hypoxic, over-oxidative, and pro-inflammatory microenvironment in the hematoma leads to oxidative stress, hyperosmotic shock, energy depletion, and Cl- removal in erythrocytes that eventually triggers eryptosis. In addition, eryptosis following intracerebral hemorrhage favors hematoma clearance, which sheds light on a common mechanism of intrinsic phagocytosis. In this review, we summarize the canonical mechanisms of eryptosis and discuss its pathological conditions associated with hemorrhagic stroke. Understanding the role of eryptosis in hemorrhagic stroke may uncover additional potential interventions for further translational clinical research.